2005
DOI: 10.1159/000089666
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mannose-Binding Lectin Levels in Maintenance Hemodialysis Patients: Impact on All-Cause Mortality

Abstract: Background/Aims: Mannose-binding lectin (MBL) is characteristic of an acute-phase-reacting protein like C-reactive protein (CRP). However, the prognostic value of the serum MBL level has not been examined. The aim of this study was to evaluate whether the serum MBL level can predict all-cause mortality in hemodialysis (HD) patients. Methods: A total of 131 patients without active infection, who had been on maintenance HD for at least 2 years, were included in this study. The serum MBL, high-sensitivity CRP (hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 52 publications
5
20
0
Order By: Relevance
“…However, inasmuch as oligomer MBL is characteristic of positive acute-phase proteins like CRP, functional and oligomer MBL levels showed no correlations with CRP levels. Interestingly, in a report by Akbari et al [35], the correlation between MBL and CRP levels was not significant in HD patients, which concurred with the correlation between oligomer MBL and high-sensitivity CRP levels found in our previous study [34]. MBL and CRP are both primarily synthesized in the liver, and levels of proinflammatory cytokines such as interleukin-6, interleukin-1 and tumor necrosis factor-α are generally affected.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, inasmuch as oligomer MBL is characteristic of positive acute-phase proteins like CRP, functional and oligomer MBL levels showed no correlations with CRP levels. Interestingly, in a report by Akbari et al [35], the correlation between MBL and CRP levels was not significant in HD patients, which concurred with the correlation between oligomer MBL and high-sensitivity CRP levels found in our previous study [34]. MBL and CRP are both primarily synthesized in the liver, and levels of proinflammatory cytokines such as interleukin-6, interleukin-1 and tumor necrosis factor-α are generally affected.…”
Section: Discussionsupporting
confidence: 90%
“…The oligomer MBL levels were measured with a commercial ELISA kit (MBL oligomer ELISA kit; BioProto Diagnostics). Previously, the serum oligomer MBL levels were measured by an ELISA using polyclonal rabbit IgG and a monoclonal antibody directed against MBL (3E7) [31,32,33,34]. Both primary and secondary antibodies were different using the two ELISA methods.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported to some extent by the results of a large Danish population-based follow-up study (8 to 24 yr) of approximately 10,000 adults that showed that MBL deficiency is not a major risk factor for morbidity and death (46). However, our results are in contrast with the Japanese 3-yr follow-up study of hemodialysis patients that showed lower serum MBL concentrations in nonsurvivors (15). To our knowledge, no other study has addressed the possible associations between MBL, MASP-2, and MASP-3 and CV end points in RTR, and further studies obviously are needed.…”
Section: No Significant Adverse Prognostic Effects Of Mbl Masp-2 Ansupporting
confidence: 81%
“…MBL has been suggested to have beneficial effects on atherosclerotic events (14), and the serum MBL levels were significantly lower among nonsurvivors than survivors in a recently published 3-yr follow-up study of 131 Japanese hemodialysis patients (15). Furthermore, Fiane et al (16) demonstrated that MBL deficiency (Ͻ100g/L) was associated with allograft vasculopathy and acute rejection in human heart transplant recipients.…”
Section: T Generally Is Accepted That Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…Infection arises as a result of bacteremia from reduced opsonophagocytic killing and reduced lectin complement pathway activation (Moller-Kristensen, et al, 2006, Shi, et al, 2004). Recent clinical studies have reported an association of MBL deficiency with increased morbidity and mortality (Garred, et al, 1999, Mullighan and Bardy, 2004, Satomura, et al, 2006, Tran, et al, 2007). …”
Section: Introductionmentioning
confidence: 99%